2021
DOI: 10.21203/rs.3.rs-322457/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differences in Functionality Between Independent, Slight, and Moderate Dependent Older Adults: A Cross-sectional Study

Abstract: Background: Aging is a gradual process characterized by damage to the physiological functions that frequently lead to dependence in the older adults of 60 years or older. We hypothesize significant differences in mental and physical capacity between fully independent older adults and slight to moderate dependent older adults. Method: A cross-sectional analysis of 322 older adults of 60 years or more, with a Barthel Index equal to or higher than 60, who attended day centers during August 2018 in Santiago-Chile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Community-based long-term care was shown to significantly improve older people's quality of life in England (Forder, Gousia, and Saloniki, 2019). Services provided at day care centers in Chile, including physical and mental exercises, significantly improved physical and cognitive outcomes (Valenzuela et al, 2021). Barnay and Juin (2016) found that formal long-term care improves older people's mental health indicators.…”
Section: Relationship Between Quality Of Life and Social Protection: ...mentioning
confidence: 99%
“…Community-based long-term care was shown to significantly improve older people's quality of life in England (Forder, Gousia, and Saloniki, 2019). Services provided at day care centers in Chile, including physical and mental exercises, significantly improved physical and cognitive outcomes (Valenzuela et al, 2021). Barnay and Juin (2016) found that formal long-term care improves older people's mental health indicators.…”
Section: Relationship Between Quality Of Life and Social Protection: ...mentioning
confidence: 99%